2019
DOI: 10.1002/slct.201803399
|View full text |Cite
|
Sign up to set email alerts
|

Single and Binary Adsorption of Zn (II) and Cr (VI) Heavy Metals onto Synthesized Silica ‐Based MCM‐41

Abstract: Effluents from numerous Industries like textile, paint, pharmaceutical, steel and electroplating industries liberate both Zinc [Zn (II)] and Chromium [Cr (VI)] heavy metals. In this work, adsorptive interaction of toxic Zn (II) heavy metal in aqueous solution with synthesized mesoporous silica based MCM‐41 was investigated. Further, the effects of presence of Cr (VI) heavy metal on the adsorption of Zn (II) and vice versa were investigated by simultaneous competitive binary adsorption from Cr (VI) and Zn (II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…41 (MCM-41), Zn( ii ), and Cr( vi ) ions were removed from single- and binary solute systems. 143 The Zn( ii ) and Cr( vi ) ions were effectively removed under the optimal working conditions of pH 7.00, 0.10 g L −1 adsorbent load and 2.00 h of contact time. It was found that raising the initial Zn( ii ) amount caused the uptake capacity of Zn( ii ) to improve, whereas increasing the Cr( vi ) concentration triggered the uptake capacity of Zn( ii ) to decrease.…”
Section: Competitive Decontamination Of Heavy Metals From Sorption Sy...mentioning
confidence: 98%
“…41 (MCM-41), Zn( ii ), and Cr( vi ) ions were removed from single- and binary solute systems. 143 The Zn( ii ) and Cr( vi ) ions were effectively removed under the optimal working conditions of pH 7.00, 0.10 g L −1 adsorbent load and 2.00 h of contact time. It was found that raising the initial Zn( ii ) amount caused the uptake capacity of Zn( ii ) to improve, whereas increasing the Cr( vi ) concentration triggered the uptake capacity of Zn( ii ) to decrease.…”
Section: Competitive Decontamination Of Heavy Metals From Sorption Sy...mentioning
confidence: 98%
“…Some of these methods had significant drawbacks, such as the production of sludge, high cost, or limited operational conditions. In contrast, the adsorption method seems to be one of the most practical choices because of its feasibility, low cost, and simple operation. , Thus, the synthesis of an adsorbent with a high affinity toward heavy metals removal was vastly investigated. , Many kinds of adsorbents, including carbon-based composites, activated carbon, nanoparticles, and clays, are used to remove heavy metals from wastewater. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Cobalt ions are naturally occurring hazardous metals found in numerous sewage and wastes from industrial effluent. The deleterious effects of this ion can lead to plants and animals deaths and many human body diseases 5,6 . The “World Health Organization‐Environmental Protection Agency” has recommended a permitted level of cobalt content of 15 μg/L in aquatic systems 7–15 .…”
Section: Introductionmentioning
confidence: 99%
“…The deleterious effects of this ion can lead to plants and animals deaths and many human body diseases. 5,6 The "World Health Organization-Environmental Protection Agency" has recommended a permitted level of cobalt content of 15 μg/L in aquatic systems. [7][8][9][10][11][12][13][14][15] Several methods have been used to recover and isolate heavy metal ions from multielement solution such as chemical treatments, ion changes, membrane processes, flocculation, and electrochemical, and adsorption techniques.…”
Section: Introductionmentioning
confidence: 99%